2023
DOI: 10.1161/strokeaha.122.041355
|View full text |Cite|
|
Sign up to set email alerts
|

Receipt of Mental Health Treatment in People Living With Stroke: Associated Factors and Long-Term Outcomes

Abstract: BACKGROUND: Untreated poststroke mood problems may influence long-term outcomes. We aimed to investigate factors associated with receiving mental health treatment following stroke and impacts on long-term outcomes. METHODS: Observational cohort study derived from the Australian Stroke Clinical Registry (AuSCR; Queensland and Victorian registrants: 2012–2016) linked with hospital, primary care billing and pharmaceutical dispensing claims data. Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…Similar to other research, 15 Tjokrowijoto et al 13 identified men, older adults, and those with no prior history of mental health treatment as being less likely to receive mental health treatment poststroke. Requiring interpretive services and holding a health benefits card were barriers to receiving psychological support independent of medication prescribed.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Similar to other research, 15 Tjokrowijoto et al 13 identified men, older adults, and those with no prior history of mental health treatment as being less likely to receive mental health treatment poststroke. Requiring interpretive services and holding a health benefits card were barriers to receiving psychological support independent of medication prescribed.…”
supporting
confidence: 63%
“…To think this an isolated problem would be amiss: a nationally representative survey study in the United States (2004-2017) found that approximately two-thirds of persons with stroke who screened positive for depression received no outpatient treatment during a calendar year. 14 Similar to other research, 15 Tjokrowijoto et al 13 identified men, older adults, and those with no prior history of mental health treatment as being less likely to receive mental health treatment poststroke. Requiring interpretive services and holding a health benefits card were barriers to receiving psychological support independent of medication prescribed.…”
Section: See Related Article P 1519supporting
confidence: 53%
See 3 more Smart Citations